Empowering Students Using Cooperative Learning Strategies Through STAD in Reading Class - Ningrum, Ary Setya Budhi; Ompumona, Cindona; Syaifulloh, Burhanudin; Addeq, Mona (Indonesian Journal of Multidisciplinary Educational Research, 2024)
This study aims to determine the use of Student Team Achievement Divison (STAD) method can improve students' reading skills. This research uses Classroom Action Research (CAR). The sample of this study were students of class VII H MTsN 5 Nganjuk in the 2021/2022 school year. The instruments used in this study were tests, observations and field notes with the number of samples used, namely 29 students. Data collection in this study used tests, observations and documentation. Data analysis in this study used quantitative analysis. The data analyzed were the mean score of the students' scores, the percentage of students' success, and the results of the observation sheet. This research has two cycles. The results of the research in the first cycle of the class average score was 66.66 with students of success of 58%. While the average value of the class in the second cycle is 78.44 with students of success is 80%. The use of Student Team Achievement Divison (STAD) method can improve the reading ability of students of class VII H at MTsN 5 Nganjuk.